Managing Mobile Devices in an Organization - Sydorenko, Z. (ХНУРЕ, 2024)
Questions regarding the use of Mobile Device Management systems in the organization are considered. The main areas of application of MDM technology are considered, an analysis of advantages and disadvantages, problematic issues of implementation is carried out. A consistent and clear approach in the implementation and configuration of MDM policies that meet the business goals of the organization will allow solving problems when using mobile devices
Keywords: data protection; Mobile Device; Mobile Device Management; security policies